The potential neuroprotective effect of Manuka Honey in Sprague-Dawley rats with Lipopolysaccharide induced neuronal injury - Bester, Janette (University of Pretoria, 2022)
Dissertation (MSc (Human Physiology))--University of Pretoria, 2021.